Cu-phthalocyanine-mediated nanowindow production on single-wall carbon nanohorn. (18th August 2021) - Stevic, Dragana; Furuse, Ayumi; Vallejos-Burgos, Fernando; Kukobat, Radovan; Kaneko, Katsumi
Abstract : We report a route for opening nanowindows on graphene wall of single wall carbon nanohorn (SWCNH) aided by copper (II) 2, 3, 9, 10, 16, 17, 23, 24-octakis (octyloxy)-29H, 31H-phthalocyanine (CuPc), which acts as a catalyst for nanowindow formation. CuPc is adsorbed on SWCNH from liquid phase and heat treated in oxygen atmosphere to produce nanowindows on the adsorption sites of CuPc. The adsorption isotherms of N2 and Ar on the CuPc-adsorbed SWCNH heat-treated have a low pressure adsorption hysteresis. The low pressure adsorption hysteresis gap of the adsorbed amount difference between the desorption and adsorption branches reaches a maximum at 573 K for both N2 and Ar adsorption. This marked low pressure adsorption hysteresis evidences formation of nanowindows whose size is comparable to the N2 and Ar molecules (0.33–0.34 nm). GRAPHICAL ABSTRACT: UF0001